Novel fluorescent probes of 10-hydroxyevodiamine: autophagy and apoptosis-inducing anticancer mechanisms - Shuqiang Chen; Guoqiang Dong; Shanchao Wu; Na Liu; Wannian Zhang; Chunquan Sheng (Elsevier, 2019)
Natural product evodiamine and its derivatives represent a promising class of multi-target antitumor agents. However, the clinical development of these compounds has been hampered by a poor understanding of their antitumor mechanisms. To tackle this obstacle, herein, novel fluorescent probes were designed to elucidate the antitumor mode of action of 10-hydroxyevodiamine. This compound was proven to be distributed in the mitochondria and lysosomes and to act by autophagy and apoptosis mechanisms. KEY WORDS: Fluorescent probes, 10-Hydroxyevodiamine, Anticancer mechanisms, Autophagy, Apoptosis